Does plyometric training improve swim start performance? - Gutierrez, G. M.; Macbeth, E. V.; Tillman, M. D.; Chow, J. W. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
For both swim starts, six out of nine variables were significantly different as a result of training. Overall improvements were seen, but were quite variable. Based on the findings of this study, it is evident that plyometric training is not a detriment to a swim training program. It cannot be conclusively determined whether plyometrics actually improve swim start performance. Further testing in a more controlled environment may elicit more significant results.